Analysis of the Application of the Principles of the Cooperative Law Environmentally Friendly in Coffee Agricultural Products (Case Study of Solok Radjo, Solok Regency) - A Hadian Pratama Hamzah; Nurhasanah Nurhasanah (JED (Jurnal Etika Demokrasi), 2022)
The purpose of this study was conducted as an effort to describe the description process related to the application of cooperative principles that are managed in an environmentally friendly manner through a cultural approach and local wisdom of the community in the Solok Radjo Cooperative, this study resulted in a study related to the level of application of cooperative principles carried out by the community in results in accordance with philosophy of law. At the analysis stage of this study using descriptive method techniques through observations on case objects (Case Study). In collecting and collecting data, questionnaires and interviews were used as a way of collecting data for this research, so that there are two forms of data, namely primary and secondary. The samples in this study were the people who were registered as members of the cooperative, then the results of data processing were strengthened based on observations from interviews with cooperative managers. Based on the results of the research and referring to the literature reviewing this research resulted in an illustration that the Solok Radjo Cooperative has properly implemented the cooperative principles according to the Cooperative Law Article 5 of Law Number 25 of 1992 in the process of implementing cooperative activities and involving the community in environmentally friendly management in the process. agricultural production with an approach to the value of local wisdom and knowledge of the indigenous Minang people.